Estudo da penetração de cloretos em compósitos cimentíciosproduzidos com aditivos redutores de permeabilidade por cristalizaçãocapilar - Carla Dabian de Oliveira (2018)
The penetration of chloride ions through concrete is one of the mechanisms capable of destabilizing the passive layer of the steel triggering the corrosion of the reinforcement, considered one of the most severe pathological manifestations in reinforced concrete structuresand directly related to durability and service life of these structures. The concrete is the physical and chemical protective barrier of the reinforcement, so, it is important to improve studies related to the reduction of penetration of aggressive agents through concrete. The introduction of additives that reduce the permeability to the mixture has been one of the options in reducing the penetration of agents through cementitious matrix, modifying the internal structure due to crystals activated by moisture and oxygen. The present study sought to evaluate the performance of waterproofing systems by capillary crystallization of concrete against the penetration of chlorides. For this reason, six mixtures were prepared, with three types for each one of the class of environmental aggressiveness II and III of NBR 6118 (ABNT, 2014) withratio b/w of 0.60 and 0.55, respectively, and using in both classes the initial high resistance Portland cement (CP V). Cylindrical test specimens with dimensions (100 x 200) mm after submerged curing were reduced in cylindrical slices of (100 x 50) mm and taken to the migration test prescribed by the NT Build 492 standard. Water absorption tests by capillarity, water absorption, voids and some mechanical tests were also used for better characterization of concretes. The results showed that the additives used produced improvements in some of the properties analyzed. In particular, it was observed the increasing resistance to chloride ion penetration and the reduction of the water absorption by capillarity. It was noted, however, that the most significant improvements were due to the reduction of the b/w ratio, established according to the classes of environmental aggression adopted.